Free-Living Energy Balance Behaviors Are Associated With Greater Weight Loss During a Weight Loss Program - Myers, Anna; Camidge, Diana; Croden, Fiona; Gibbons, Catherine; Stubbs, R. James; Blundell, John; Finlayson, Graham; Buckland, Nicola (Frontiers in Nutrition, 2021)
Introduction: Free-living movement (physical activity [PA] and sedentary behaviour [SB]) and eating behaviours (energy intake [EI] and food choice) affect energy balance and therefore have the potential to influence weight loss (WL). This study explored whether free-living movement and/or eating behaviours measured early (week 3) or late (week 12) in a 14-week WL programme are associated with diet-induced WL in women. Methods: Eighty women (M±SD age: 42.0±12.4 years) with overweight or obesity [body mass index (BMI): 34.08 ± 3.62 kg/m2] completed a 14-week WL programme focused primarily on diet. Body mass (BM) was measured at baseline, and again during week 2 and 14 along with body composition. Free-living movement (SenseWear Armband) and eating behaviour (weighed food diaries) were measured for one-week during week 3 and 12. Hierarchical multiple regression analyses examined whether free-living movement and eating behaviours were associated with WL. Differences in behaviour between clinically significant weight losers (CWL; ≥ 5% WL) and non-clinically significant weight losers (NWL; ≤ 3% WL) were compared. Results: Energy density of food consumed [β = 0.45, p < .001] and vigorous PA [β = -0.30, p < .001] early in the intervention and early-late change in light PA [β = -0.81 p < .001], moderate PA [β = -1.17 p < .001], vigorous PA [β = -0.49, p < .001], total energy expenditure (EE) [β = 1.84, p < .001] and energy density of food consumed [β = 0.27, p = .01] significantly predicted % BM change. Early in the intervention CWL consumed less energy dense foods than NWL [p = .03]. CWL showed a small but significant increase in vigorous PA whereas NWL showed a slight decrease [p =.04]. Conclusion: Early and early-late change in free-living movement and eating behaviours during a 14-week WL programme are predictors of WL. These findings demonstrate that specific behaviours that contribute to greater EE (e.g., vigorous PA) and lower EI (e.g., less energy dense foods) are related to greater WL outcomes. However, dietary assessments are likely to have bene confounded by misreporting of EI. Interventions targeting these behaviours may increase the effectiveness of diet-induced WL programmes.